POLITICAL THOUGHT ABU AL-A’LA AL POLITICAL THOUGHT ABU AL-A’LA AL-MAUDUDI - Harianto, Nurul (Program Studi Ilmu Tasawuf Universitas Pangeran Diponegoro Nganjuk, Jawa Timur, 2025)
Abstract Abu Al-A’la Bin Hasan al-Maududi (namely al-Maududi)is a figure as novelty thought and modern phenomenal Islamic Da’i, al-Maududi is a figure who intends on raising his ideas as a novelty. The most interesting on Al-Maududi's book is thought consistency and their ability to combine and compose his thought as a system or right thought structure and integrated. Therefore he can raise Islamic study easy understanding. Many Islamic through from India-Pakistan such as Syeikh Waliyullah, Sir Sayyid Ahmad Khan, Amir Ali, Yusuf Ali, Muhammad Iqbal, Fazlu al-Rahman etc. Al-Maududi is persistent and persevering on creating a comprehensive system in Islam for human life, although, he gets criticism from other philosophers, unshakable his. Keywords: Al-Maududi, Islamic thought, Modern thought